2018
DOI: 10.1177/0040517518755789
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of flax/polypropylene commingled nonwoven at dry scale: Influence of process parameters

Abstract: Currently, nonwoven fabrics made with natural and thermoplastic commingled fibers have been extensively used in the composite industry due to their light weight and low processing and material costs. As two key parameters in the manufacturing of nonwoven fabrics, the needle-punching and material surface densities influence strongly the mechanical properties of nonwoven fabrics and their reinforced composite parts. Compared to most studies focused on the composite stage, the present experimental investigation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Few studies have been conducted regarding the evolution of the needle punching density of the isotropy ratio among these mechanical properties in the main directions (MD/CD) of nonwoven materials. A previous paper [35] associated with an experimental study conducted at the dry scale with the same materials has shown that the needle-punching density can influence the anisotropy of nonwoven fabrics. The purpose of this new paper is to analyse the mechanical behaviour of nonwoven reinforced Flax/PP by tensile and flexural tests conducted at the scale of composites after the hot moulding process.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been conducted regarding the evolution of the needle punching density of the isotropy ratio among these mechanical properties in the main directions (MD/CD) of nonwoven materials. A previous paper [35] associated with an experimental study conducted at the dry scale with the same materials has shown that the needle-punching density can influence the anisotropy of nonwoven fabrics. The purpose of this new paper is to analyse the mechanical behaviour of nonwoven reinforced Flax/PP by tensile and flexural tests conducted at the scale of composites after the hot moulding process.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile properties are mainly influenced by needle-punching parameters (depth of needle-punching and needle-punching density). Gnaba et al [110] have recently demonstrated for Flax/PP non-woven that an increase of the maximum tensile strain can be related to the increase in the needle-punching density. In addition, increasing the needle-punching density leads to a decrease of the anisotropy ratio of the tensile behaviour between the MD and the CD.…”
Section: Propertiesmentioning
confidence: 99%
“…Bio-composites generally consist of petroleum-based matrix and natural reinforcement materials [5]. Biocomposites containing natural fibers have become increasingly important considering the difficulties in plastic disposal and the overuse of petroleum resources [6]. The use of recycled natural fiber reinforcement takes this issue one step further.…”
Section: Introductionmentioning
confidence: 99%